1999
DOI: 10.1073/pnas.96.18.10320
|View full text |Cite
|
Sign up to set email alerts
|

A physical complex of the Fanconi anemia proteins FANCG/XRCC9 and FANCA

Abstract: Fanconi anemia (FA) is a recessively inherited disease characterized at the cellular level by spontaneous chromosomal instability and specific hypersensitivity to cross-linking agents. FA is genetically heterogeneous, comprising at least eight complementation groups (A-H). We report that the protein encoded by the gene mutated in complementation group G (FANCG) localizes to the cytoplasm and nucleus of the cell and assembles in a molecular complex with the FANCA protein, both in vivo and in vitro. Endogenous F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
115
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(122 citation statements)
references
References 35 publications
5
115
0
2
Order By: Relevance
“…Recent work has found the FANCE, FANCF, FANCG, and FANCL proteins in the complex as well (31)(32)(33)(34). A large complex is suggested by our recent work (35), and binding does not occur in any of the complementation groups except the FA-D1, D2, I, and J groups (7).…”
mentioning
confidence: 69%
“…Recent work has found the FANCE, FANCF, FANCG, and FANCL proteins in the complex as well (31)(32)(33)(34). A large complex is suggested by our recent work (35), and binding does not occur in any of the complementation groups except the FA-D1, D2, I, and J groups (7).…”
mentioning
confidence: 69%
“…We have observed interdependence of protein signals in immunoblots in other patients of both FA-A and FA-G complementation groups. 14 Of 35 assigned German families, nine belong to complementation group FA-G making this the second largest group in Germany after FA-A (68%). The 313G → T mutation accounts for 44% of the alleles in German FA-G patients and is clearly due to a founder effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that FANCG is found in the cells as a nuclear complex with the FANCA protein. 14,15 Pathogenic mutations in FANCG were previously reported in four FA-G patients, we report here further mutations in 16 FA-G patients, including common German and Turkish founder mutations.…”
Section: Introductionmentioning
confidence: 97%
“…Together, our results suggest that the FANCA-FANCG interaction may occur through intermolecular disulfide linkage(s) in a oxidative damage-dependent manner. protein complex (4,14,27), and FANCG (XRCC9) protein is required for binding of the FANCA and FANCC proteins (4,14), suggesting that FANC proteins form a large multiprotein complex that may be necessary for their function in damage signaling and repair. In this study we examined the interaction of FANC proteins in response to oxidative stress.…”
Section: Fanca-fancg Interaction Is Significantly Enhanced In Responsmentioning
confidence: 99%